1994
DOI: 10.2307/1131387
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Experiences of Young Children and the Quality of Their Home Environments

Abstract: This paper assesses the relative contribution of maternal, household, child, and poverty characteristics to the quality of the home environment. The sample consists of 1,887 children birth to 4 years old from the National Longitudinal Survey of Youth (NLSY). Ordinary least-squares regression is used to explore conceptually distinct aspects of children's poverty experiences. Poverty variables are found to have a statistically significant effect on the quality of the home environment, after controlling for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 25 publications
(31 reference statements)
2
40
0
3
Order By: Relevance
“…Experiments both with animals and with children have demonstrated that secure attachment and an enriched environment for development are protective factors. 9,15,[27][28][29][30] By means of a psychosocial stimulation program aimed at mothers, Eickmann et al 15 recorded a significant increase in the mental and motor development indexes, as assessed using Bayley II at 18 months, in the group that received the intervention, compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments both with animals and with children have demonstrated that secure attachment and an enriched environment for development are protective factors. 9,15,[27][28][29][30] By means of a psychosocial stimulation program aimed at mothers, Eickmann et al 15 recorded a significant increase in the mental and motor development indexes, as assessed using Bayley II at 18 months, in the group that received the intervention, compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As a proxy for maternal intelligence, which is an important contributing factor for child development, we used the TVIP to measure working vocabulary of the caregiver. 30 Household-level socio-demographic data-The following household-level information was obtained at baseline: composition of the household (i.e. age and sex of all family members), father's education, number of people in the household, whether an indigenous language was spoken in the home, presence of electricity and water in the household and number of small and draft animals owned.…”
Section: Covariatesmentioning
confidence: 99%
“…While wealthier families are able to purchase materials, experiences, and services to invest in their children (e.g., books, computers, educational outings to museums, or tutoring) (Garrett et al 1994), children from families with limited resources may not have access to these investments. Furthermore, these families' housing conditions may not be conducive to learning (e.g., poor lighting, limited space, or high noise levels) (Dearing and Taylor 2007;Evans 2004).…”
Section: Poverty Limits Learning and Academic Achievementmentioning
confidence: 99%